The role of peg 6000 and pvp as stabilizing and surfactant agents in the photoelectrochemical properties of bivo4 monoclinic structure - Pelissari, Marcelo R.S. [UNESP]; Scalvi, Luis Vicente A. [UNESP]; Dall'Antonia, Luiz Henrique (Sociedade Brasileira de Quimica (SBQ), 2021)
Nanocrystalline BiVO4 on monoclinic phase was obtained by a modified-solution combustion synthesis (SCS) using poly(ethylene glycol) (PEG 6000) and polyvinylpyrrolidone (PVP) as stabilizing and surfactant agents, respectively. An active photoanode was built using a simple procedure by dip-coating deposition process on fluorine-doped tin dioxide (FTO). The structure, morphology and optical properties of FTO/BiVO4 photoanode were evaluated by means of X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM) and diffuse reflectance UV-Vis spectroscopy. The photoelectrochemical performance measurements were carried out by linear sweep voltammetry (LSV), chronoamperometry and electrochemical impedance spectroscopy (EIS) under InGaN blue light emitting diode (LED) illumination condition (about 450 nm). In Na2SO4 electrolyte solution, the electrode has presented better photoelectroactivity than in NaNO3 solution, as evidenced by photoelectrochemical parameters such as: The highest photocurrent density (js) value, cathodic shifts of the onset potential (OP) and lower charge-transfer resistence (Rct). In the methyl orange (MO) degradation reaction the FTO/BiVO4 electrode has presented high photoelectroactivity, where the estimated kinetic constant rate (kobs) is 4.74 × 10-3 and 7.54 × 10-3 min-1 in NaNO3 and Na2SO4 solutions, respectively. This remarkable performance of the as-prepared electrode is due to the morphological BiVO4 structure, with elongated-shape nano-sized domain particles, besides the considerable porosity and roughness levels on electrode surface.
Keywords: Dip-coating process; Monoclinic BiVO4; PEG 6000; Photoelectrochemical performance; PVP; SCS